A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMA YLPI PERHENTIAN MARPOYAN PEKANBARU IN COMPLETING SENTENCES WITH CORRECT VERB FORMS - Aswandi Aswandi (Politeknik Negeri Bengkalis, 2017)
Abstract: learning English cannot be separated from learning grammar. In grammar the students learn about many things, such as sentence patterns and the combination of words and phrases. Most students faced difficulty in applying correct grammar. This study aimed to find out the students ability in selecting correct verb forms.This research was a descriptive research. This study showed that the level of students ability was at mediocre level. It was at 50.10. It also showed that the highest score obtained by the students was 75. Meanwhile, the lowest score was 32.5. The average score The error commonly occured in selecting correct â€œinfinitiveâ€ to complete the sentences.Â